2015
DOI: 10.1074/jbc.m115.661835
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac RNA Induces Inflammatory Responses in Cardiomyocytes and Immune Cells via Toll-like Receptor 7 Signaling

Abstract: Background: Necrotic extracellular RNA induces inflammation and may contribute to ischemic myocardial injury, but the underlying mechanism is unclear. Results: Isolated cardiac RNA induced cytokine production in cardiomyocytes/immune cells as well as acute peritonitis. Genetic deletion of TLR7 or MyD88 markedly attenuates RNA-mediated cytokine production. Conclusion: Cellular RNA induces cytokine production via TLR7-MyD88 signaling. Significance: Cardiac RNA is a pro-inflammatory mediator sensed by TLR7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 48 publications
(52 reference statements)
1
61
0
Order By: Relevance
“…Increased level of eRNA was demonstrated in bronchoalveolar lavage fluids of patients suffering from acute respiratory distress syndrome (ARDS)47. This eRNA may participate in ARDS pathogenesis by increasing permeability of epithelia-capillary barrier48, enhancing intraalveolar fibrin deposition22234749 and stimulating the production and release of proinflammatory cytokines2223262749. Here, we propose a novel function of eRNA, which promotes S. pneumoniae infection and the development of pneumonia, a well-described direct cause of ARDS50.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased level of eRNA was demonstrated in bronchoalveolar lavage fluids of patients suffering from acute respiratory distress syndrome (ARDS)47. This eRNA may participate in ARDS pathogenesis by increasing permeability of epithelia-capillary barrier48, enhancing intraalveolar fibrin deposition22234749 and stimulating the production and release of proinflammatory cytokines2223262749. Here, we propose a novel function of eRNA, which promotes S. pneumoniae infection and the development of pneumonia, a well-described direct cause of ARDS50.…”
Section: Discussionmentioning
confidence: 98%
“…Extracellular nucleic acids were found to induce humoral and cellular immune responses during infection and to promote the formation of fibrin that entraps invading microbes202122. In particular, host-derived eRNA was reported to: i) enhance fibrin deposition by the activation of the contact phase pathway2223, ii) increase the adhesion and transmigration of leukocytes to and across the endothelium24, iii) and, augment the release of proinflammatory cytokines such as macrophage inflammatory protein-2, interleukin-1β, −6, −10, and tumor necrosis factor α from neutrophils, bone marrow-derived macrophages and endothelial cells24252627. However, the direct interaction of host-derived eRNA with pneumococcal surface, and the potential consequences of this process on bacterial tropism have not been addressed thus far.…”
mentioning
confidence: 99%
“…55 In a recent report, however, it was demonstrated that cardiomyocytes responded to eRNA (isolated from cardiomyocytes or from heart tissue) especially in the presence of lipofectamine with by guest on May 11, 2018 http://circres.ahajournals.org/ Downloaded from the induction of inflammatory factors in a TLR7-MyD88-dependent manner. 56 Because these data were derived with the help of transfection agents, it remains to be established in which way eRNA can naturally gain access to endosomal TLR7 in the absence of such chemicals.…”
Section: Erna In Myocardial Infarction and I/r Injurymentioning
confidence: 99%
“…TLRs recognize both pathogen-associated molecular components [7, 8], such as lipopolysaccharide of gram-negative bacteria and peptidoglycan of gram-positive bacteria, and endogenous danger-associated molecular patterns, such as heat shock proteins and extracellular RNA [911]. To date, ten TLR family members in human and thirteen in mice have been identified [12].…”
Section: Introductionmentioning
confidence: 99%